Los estudios irlandeses alrededor del mundo – 2018 - Christina Hunt Mahony (Estudios Irlandeses, 2019)
As I write, Ireland’s decade of centenaries continues with eyes focused on the forthcoming First World War armistice centennial observance, along with that of the crucial 1918 Dail Election, the first election in which (some) women were enfranchised, and which ushered in an era of more radicalized politics in the country. President Michael D. Higgins, re-elected by a sizable majority in October will be sworn into office once again just hours after the solemn commemorative moment of the 11th hour of the 11th day of the 11th month. Because of its unique overlapping revolutionary history with WWI Ireland has been late in acknowledging their countrymen who fought and died in that war – thus this date is of even greater significance now.